2019
DOI: 10.7575/aiac.ijels.v.7n.3p.19
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Demographic Factors on Teachers’ Instructional Practices and Challenges in Including Students with Visual Impairment in Government Secondary Schools of Harari Region

Abstract: The purpose of this study was to examine the influence of demographic factors on instructional practices and challenges teachers face in teaching students with visual impairments in the government secondary schools of Harari regional state. A quantitative method with a survey design was employed. The sample consisted of 100 (with 95% response rate) participants selected using simple random sampling technique. Data was collected using questionnaire in the form of Likert scale. Frequencies, percentages, means, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Furthermore, this study finds that providing appropriate teaching strategies in teaching writing skills for visually impaired students is a significant issue which confirms that teachers in the respective schools need training which could enhance and improve their competency in teaching. Dea and Negassa (2019) identified that several challenges encountered by teachers in Ethiopia in teaching students with visual impairment are reflected from the availability of professional training or teacher development programs as well as the existence of learning sources which ideally contribute to support the teaching and learning process (Basaran, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study finds that providing appropriate teaching strategies in teaching writing skills for visually impaired students is a significant issue which confirms that teachers in the respective schools need training which could enhance and improve their competency in teaching. Dea and Negassa (2019) identified that several challenges encountered by teachers in Ethiopia in teaching students with visual impairment are reflected from the availability of professional training or teacher development programs as well as the existence of learning sources which ideally contribute to support the teaching and learning process (Basaran, 2012).…”
Section: Discussionmentioning
confidence: 99%